Application of hyperpolarized magnetic resonance in the study of cardiac metabolism - Tyler, D; Schroeder, M; Cochlin, L; Clarke, K; Radda, G (2008)
The application of magnetic resonance (MR) for metabolic imaging and spectroscopy has been limited by the intrinsically low sensitivity and natural abundance of 13C. Recently a method has been developed in which solid-state, dynamically polarized MR-active nuclei can be dissolved to obtain a solution polarized in excess of 20%. When used in concert with MR spectroscopy, this method of hyperpolarization provides the MR signal necessary to detect low-abundance molecules, enabling visualization of the substrate uptake and in vivo metabolism in real time. This study utilized hyperpolarized [1- 13C]pyruvate as a metabolic tracer to monitor cardiac metabolism in healthy rats in vivo. The conversion of [1- 13C]pyruvate to [1- 13C]lactate, [1- 13C]alanine and bicarbonate (H 13CO 3-) was observed with high signal-to-noise ratio at 1 s temporal resolution. The acquired spectra demonstrated that injection of hyperpolarized [1- 13C]pyruvate elicited a consistent metabolic response in vivo and displayed instantaneous information regarding the evolution of the metabolite pools of each product of pyruvate. We have demonstrated the feasibility of applying hyperpolarized MR to the study of cardiac metabolism, with a view to detecting the alterations in substrate utilization that occur in heart disease. © 2008 Springer-Verlag.